Stress loops effect in ductile failure of mild steel (2009)
A simulation study of effect of stree on mild microstructure has revealed stress loops at areas of stress application which are believed to be the root cause of the ductile failure morphology (cup and cone) in ductile alloys under plane strain conditions. The area of concerntration of these stress loops were obsrved to be that of subsequent instability (or necking) observed in mild steel and other materials of low friction (flow) stress. Shear stress loops with angular bearing of 45 o to the tensile axis were observed to instigate both the failure site and shear morphology in these materials. In plane stress conditions, shear was seen to be that of a wave shape running obliquely to area of stress application resulting in oblique necking observed in thin mild steel sheets.